Copper induces a viable but nonculturable (VBNC) state in Erwinia amylovora - Ordax, Mónica; Marco-Noales, Ester; López, María M.; Biosca, Elena G. (2017)
Copper compounds, used to control Erwinia amylovora, have a strong effect on the culturability of plant-associated bacteria. Recent studies have shown that some phytopathogenic bacteria enter into a viable but nonculturable (VBNC) state in the presence of copper. This state, in which cells progressively lose their culturability on non-selective solid media, is considered to be a survival strategy under adverse environmental conditions. To determine whether copper kills or induces a VBNC state in E. amylovora cells, mineral medium without copper or supplemented with 0.005, 0.01 and 0.05 mM Cu2+ was inoculated with 10(7) cfu/ml of the pathogen. Aliquots were taken regularly for four months, and the total and viable cell counts were determined using the Live/Dead staining kit and culturable cell counts were determined on King's B medium. E. amylovora entered into a VBNC state in the presence of the three copper concentrations assayed. It entered faster the VBNC state with increased copper concentration: it entered at days 36, 1 and 0 (immediately after being introduced in the medium) with 0.005, 0.01 and 0.05 mm Cu2+ respectively. Afterwards, the restoration of culturability or resuscitation of copper-induced VBNC E. amylovora cells was achieved by the addition of different copper complexing agents that could remove the free-copper ions. Dilution studies were also performed to demonstrate that the resuscitated cells came from a true resuscitation and not from the regrowth of any undetectable culturable cell. Finally, the pathogenicity of both VBNC and resuscitated cells was evaluated by inoculation on immature pear fruits. Copper-induced VBNC cells were virulent only for five days while resuscitated cells held their pathogenicity for more than four months. Understanding the effect of copper against E. amylovora cells could help to optimize fireblight control strategies.